The heiress : a novel [large type] - Hawkins, Rachel, 1979- (Thorndike Press large print top shelf., 2024)
"When Ruby McTavish Callahan Woodward Miller Kenmore dies, her adopted son, Camden, rejects his inheritance, settling into a normal life as an English teacher in Colorado and marrying Jules, a woman just as eager to escape her own messy past. Ten years later, his uncle's death pulls Cam and Jules back into the family fold and questions about the infamous heiress come to light. What really happened to those four husbands, who all died under mysterious circumstances? And why did she adopt Cam in the first place? Soon, Jules and Cam realize that an inheritance can entail far more than what's written in a will--and that the bonds of family stretch far beyond the grave"--